Protective role of quercetin against manganese-induced injury in the liver, kidney, and lung; and hematological parameters in acute and subchronic rat models - Bahar E; Lee GH; Bhattarai KR; Lee HY; Kim HK; Handigund M; Choi MK; Han SY; Chae HJ; Yoon H (Dove Medical Press, 2017)
Entaz Bahar,1 Geum-Hwa Lee,2 Kashi Raj Bhattarai,2 Hwa-Young Lee2 Hyun-Kyoung Kim,2 Mallikarjun Handigund,3 Min-Kyung Choi,2 Sun-Young Han,1 Han-Jung Chae,2 Hyonok Yoon1 1College of Pharmacy, Research Institute of Pharmaceutical Sciences, Gyeongsang National University, Jinju, 2Department of Pharmacology, Medical School, Chonbuk National University, 3Department of Laboratory Medicine, Chonbuk National University Hospital, Jeonju, Republic of Korea Abstract: Manganese (Mn) is an important mineral element required in trace amounts for development of the human body, while over- or chronic-exposure can cause serious organ toxicity. The current study was designed to evaluate the protective role of quercetin (Qct) against Mn-induced toxicity in the liver, kidney, lung, and hematological parameters in acute and subchronic rat models. Male Sprague Dawley rats were divided into control, Mn (100 mg/kg for acute model and 15 mg/kg for subchronic model), and Mn + Qct (25 and 50 mg/kg) groups in both acute and subchronic models. Our result revealed that Mn + Qct groups effectively reduced Mn-induced ALT, AST, and creatinine levels. However, Mn + Qct groups had effectively reversed Mn-induced alteration of complete blood count, including red blood cells, hemoglobin, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, platelets, and white blood cells. Meanwhile, the Mn + Qct groups had significantly decreased neutrophil and eosinophil and increased lymphocyte levels relative to the Mn group. Additionally, Mn + Qct groups showed a beneficial effect against Mn-induced macrophages and neutrophils. Our result demonstrated that Mn + Qct groups exhibited protective effects on Mn-induced alteration of GRP78, CHOP, and caspase-3 activities. Furthermore, histopathological observation showed that Mn + Qct groups effectively counteracted Mn-induced morphological change in the liver, kidney, and lung. Moreover, immunohistochemically Mn + Qct groups had significantly attenuated Mn-induced 8-oxo-2´-deoxyguanosine immunoreactivity. Our study suggests that Qct could be a substantially promising organ-protective agent against toxic Mn effects and perhaps against other toxic metal chemicals or drugs. Keywords: manganese, quercetin, liver, kidney, lung, hematological parameters